Parent Management Training—Oregon Model: Adapting Intervention with Rigorous Research. Issue 3 (10th June 2016) - Forgatch, Marion S.; Kjøbli, John
Abstract : Parent Management Training—Oregon Model (PMTO ® ) is a set of theory‐based parenting programs with status as evidence‐based treatments. PMTO has been rigorously tested in efficacy and effectiveness trials in different contexts, cultures, and formats. Parents, the presumed agents of change, learn core parenting practices, specifically skill encouragement, limit setting, monitoring/supervision, interpersonal problem solving, and positive involvement. The intervention effectively prevents and ameliorates children's behavior problems by replacing coercive interactions with positive parenting practices. Delivery format includes sessions with individual families in agencies or families' homes, parent groups, and web‐based and telehealth communication. Mediational models have tested parenting practices as mechanisms of change for children's behavior and found support for the theory underlying PMTO programs. Moderating effects include children's age, maternal depression, and social disadvantage. The Norwegian PMTO implementation is presented as an example of how PMTO has been tailored to reach diverse populations as delivered by multiple systems of care throughout the nation. An implementation and research center in Oslo provides infrastructure and promotes collaboration between practitioners and researchers to conduct rigorous intervention research. Although evidence‐based and tested within a wide array of contexts and populations, PMTO must continue to adapt to an ever‐changing world. Abstract : Video Abstract